Antimalarial potential of quinones isolated from plants: an integrative review - Gomes, Antonio Rafael Quadros (2021)
Antimalarial treatment is often associated with the resistance developed by Plasmodium which generate ineffective drug treatment. Based on this, the search for therapeutic alternatives is necessary and urgent. This review intends to assess the antimalarial potential of quinones isolated from plants. The search for scientific articles was carried out on the CAPES Journal Portal (PPC), Virtual Health Library (VHL), PUBMED, NCBI and SCIELO, using the following descriptors: quinones and antimalarials. Inclusion criteria were adopted based on studies about quinones isolated from plants and tested against Plasmodium falciparum and Plasmodium berghei. The exclusion criteria were based mainly on articles that tested extracts, fractions and synthesis of quinones obtained from plants and other natural products. A total of 1344 publications were collected for screening (PPC = 5, VHL = 248, PUBMED = 525, NCBI = 462 and SCIELO = 94). From this total, 1280 articles were excluded, with only 64 articles selected for full reading. All benzoquinones were active against P. falciparum. Naphthoquinones were active, inactive and moderately active against the P. falciparum e P berghei. Anthraquinones and anthrones were active and moderately active against P. falciparum. The naphthoquinone 2-acetylnaphtho- [2,3b] -furan-4,9-dione was the most active of all the molecules tested against Plasmodium. Whereas lapachol was the most studied naphthoquinone and structural changes do not seem to contribute to the activity. In summary, quinones are promising as antimalarials, however, need in vivo studies.